DISASTER-SAFE-SCHOOL BASED PROGRAM FOR THE PSYCHOLOGICAL PREPAREDNESS OF ELEMENTARY SCHOOL STUDENTS - Alfianto, Ahmad Guntur; Wijayanti, Dini Prastyo; Sulaksono, Ari Dwi; Choirullah, Alvin Huda (Nurse and Health: Jurnal Keperawatan, 2024)
Background: Earthquake and tsunami are high risk disasters in the coastal areas of Java. The lack of psychological preparedness in coastal areas poses a threat to risk groups, especially school-aged children. Prevention efforts that can be carried out are through disaster-safe school-based programs through disaster management educational vehicles Objectives: The aim of this research was to analyze the influence of disaster-safe school-based programs on psychological preparedness in facing earthquake and tsunami disasters in school-aged children Methods: . The method used was a pre-experimental design. The sampling technique used purposive sampling with a sample size of 54 respondents. The sample was school age children who lived on the coast of Malang Regency. The measuring tool used the Psychological Preparedness for Disaster Threat Scale (PPDTS) questionnaire. The statistical test used was the paired t-test Results: The results showed that there were differences in psychological preparedness before and after school-aged children were given a school-based program that was safe from earthquake and tsunami disasters (0.000). Conclusion: The conclusion is that there is an influence/impact of disaster-safe school-based programs on the psychological preparedness of school-aged children in facing earthquakes and tsunamis.